Expression of αv Integrin in Feline Injection-Site Sarcoma (FISS): Preliminary Investigations - Andrea Cappelleri; Eleonora Brambilla; Lavinia E. Chiti; Alessia Trapletti; Gaia B. M. Bianchi; Mauro Di Giancamillo; Valeria Grieco; Chiara Giudice (Animals)
Feline injection-site sarcomas (FISSs) are malignant skin tumors of mesenchymal origin arising at local post-vaccination (or injection) sites. In recent years, a fluorescence imaging technique based on probes targeting αvβ3 integrin has been effectively applied for the surgical complete resection of the tumor. In our study, we investigated the utility of a commercially available anti-αv integrin polyclonal antibody for the histopathological evaluation of FISS’s surgical excision margins. We collected 10 formalin-fixed paraffin-embedded (FFPE) feline excisional biopsies with a histopathological diagnosis of FISS (7 fibrosarcomas and 3 pleomorphic sarcomas) and wide margin tissue, along with one subcutaneous injection-site granuloma and 6 osteosarcomas. Samples were processed for histology, and slides were stained for IHC with the anti-αv integrin antibody. Immunostained slides were evaluated for the cellular localization and intensity of the staining in different neoplastic and non-neoplastic cell populations. Neoplastic and non-neoplastic spindle cells had cytoplasmic positivity in all fibrosarcomas. Inflammatory cells, including macrophages of the injection-site granuloma, were negative. Multinucleated giant cells in the pleomorphic sarcomas had an intense membranous positivity. Although the anti-αv integrin antibody was ineffective for the histopathological evaluation of surgical excision margins, the membranous localization of αv integrin in multinucleated giant cells of pleomorphic sarcomas suggests that it plays a role in the oncogenesis of this FISS variant.